Exceptional provenance of amparo suit for payment of labor claims: a way for protection of economic, social and cultural rights - Pabón-Mantilla, Ana Patricia; Acevedo-Suárez, Aury Mayerly; Mosquera, Stella (Universidad Pedagógica y Tecnológica de Colombia, 2014)
The economic, social and cultural rights are those rights which enable an adequate level of living for the people. These rights have been the subject of universal statements (International Covenant on Economic, Social and Cultural Rights, ICESCR, 1966), and also have been recognized by our Constitution. It is important to determine that in the context of these rights we can talk about access, conditions of employment, social security, among other issues of great importance. This work aims to study the mechanisms of enforcing these rights through the development of a line of jurisprudence that seeks to determine if the non-payment of labor claims violates the right to the subsistence level, and if thus the amparo suit as a defense mechanism is feasible.